Tailored Multivalent Neo-Glycoproteins: Synthesis, Evaluation, and Application of a Library of Galectin-3-Binding Glycan Ligands - Laaf, Dominic; Bojarová, Pavla; Pelantová, Helena; Křen, Vladimír; Elling, Lothar (Bioconjugate chemistry, 2017)
Galectin-3 (Gal-3), a member of the β-galactoside-binding lectin family, is a tumor biomarker and involved in tumor angiogenesis and metastasis. Gal-3 is therefore considered as a promising target for early cancer diagnosis and anticancer therapy. We here present the synthesis of a library of tailored multivalent neo-glycoproteins and evaluate their Gal-3 binding properties. By the combinatorial use of glycosyltransferases and chemo-enzymatic reactions, we first synthesized a set of N-acetyllactosamine (Galβ1,4GlcNAc; LacNAc type 2)-based oligosaccharides featuring five different terminating glycosylation epitopes, respectively. Neo-glycosylation of bovine serum albumin (BSA) was accomplished by dialkyl squarate coupling to lysine residues resulting in a library of defined multivalent neo-glycoproteins. Solid-phase binding assays with immobilized neo-glycoproteins revealed distinct affinity and specificity of the multivalent glycan epitopes for Gal-3 binding. In particular, neo-glycoproteins decorated with N',N″-diacetyllactosamine (GalNAcβ1,4GlcNAc; LacdiNAc) epitopes showed high selectivity and were demonstrated to capture Gal-3 from human serum with high affinity. Furthermore, neo-glycoproteins with terminal biotinylated LacNAc glycan motif could be utilized as Gal-3 detection agents in a sandwich enzyme-linked immunosorbent assay format. We conclude that, in contrast to antibody-based capture steps, the presented neo-glycoproteins are highly useful to detect functionally intact Gal-3 with high selectivity and avidity. We further gain novel insights into the binding affinity of Gal-3 using tailored multivalent neo-glycoproteins, which have the potential for an application in the context of cancer-related biomedical research.
Keywords: galektin 3; Cattle; Protein Binding; glykoproteiny; Combinatorial Chemistry Techniques; ligandy; aminocukry; techniky kombinatorické chemie; skot; Oligosaccharides; Ligands; Galectin 3; Glycoproteins; vazba proteinů; Animals; lidé; oligosacharidy; Humans; zvířata; Amino Sugars; glykosylace; Serum Albumin, Bovine; sérový albumin hovězí; Glycosylation